Uso do espaço por uma população de Muriquis-do-norte (Brachyteles hypoxanthus) - Lima, Marlon (2016)
Populations of primates studied for long periods represent rare opportunities to assess how population densities and territoriality influence the use of space in isolated fragments. The population of northern muriquis (Brachyteles hypoxanthus) at RPPN Feliciano Miguel Abdala (RPPN-FMA) in Caratinga, Minas Gerais, consisted of 288 to 335 individuals divided among four social groups during the present study period from August 2010 through July 2013. We used 22,466 location points of the groups, analyzed monthly and annually, to estimate variables, such as the home ranges, core areas, day ranges, overlap areas and intergroup interactions, which are important for understanding the use of space and analyses of territoriality estimate. Home ranges varied from 146.5 ha (group Nadir) to 416.8 ha (group Matão) among the groups during the study period. Core areas ranged from 13% (group M2) to 29% (group Nadir) of the home ranges. The day ranges were similar among the four groups, indicating that they were not influenced by variation in the size of the groups. Overlapping areas between groups ranged from 0 to 66.4 ha of the home ranges, and from 0 to 7.5 ha of the core areas. Only Nadir group overlapped its core area with the other three groups and the largest overlap was with Matão group, the largest group in this population. Most intergroup interactions (73%) occurred within the core areas. Therefore, we use the defensibility index proposed by Mitani & Rodman (1979) and fractional monitoring rate of Lowen & Dunbar (1994) to test the degree of territoriality between the Matão group and neighboring groups. Our analyses indicate that the defense of the core area was much greater than that found for home ranges monthly and annually. The territorial defense of the core area suggests that population density can influence the use of space over time. To determine whether our finding of core area territoriality is a typical or atypical behavior for this species, we need comparative data from other populations. Keywords: use of space; home range; core area; day range; overlap area; territoriality